Pemberdayaan Masyarakat melalui Pengembangan Desa Wisata Organik di Kabupaten Bondowoso - Indrianti, Deditiani Tri; Ariefianto, Lutfi; Halimi, Dinar (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2019)
This research uses descriptive qualitative type, aimed at describing to empower the community of Lombok Kulon Village through the Development of Organic Tourism Village. Data collection using interviews, observation, and documentation. The validity of the data uses the triangulation of sources, techniques, and time. The results of this study were: the development of an organic tourism village program that focused on managing physical and non-physical potential had been able to make the community empowered. Community empowerment could be seen from the two indicators that had been achieved, namely participation and control. In developing this organic village tourism program, the community had participated in and controlled every activity held. The form of community participation was the involvement of the community in supporting the organic tourism village program in which it was more aware and transformed to be a better community. Finally, the control was done through the Focus Group Discussion that allowed the community to did direct sharing with the management of organic tourism village.